Preparation and Characteriazation of Bismuth Niobium Oxide Ion Conductors - Ng, Sin Nee (2009)
Materials in Bi2O3-Nb2O5 binary system have been successfully synthesized by conventional solid-state method and also mechanochemical method. Solid solution series, BixNbOδ was obtained at 2.5 ≤ x ≤ 6 for both conventional solid-state method and mechanochemical method. Bi3NbO7 was successfully obtained by mechanochemical method at lower synthesis temperature (milled at 1000 rpm for 1 hour followed by heating at 700 oC for 24 hours) than conventional solid-state method. All the peaks in the XRD patterns can be fully indexed in a tetragonal system with space group I4m2. Electrical measurements indicated that, although both the Bi3NbO7 synthesized by two different methods exhibited almost the same conductivities. However the sample prepared by mechanochemical method showed lower activation energy. Among the solid solutions prepared by two different methods, Bi5NbO10 and Bi6NbO11.5 exhibit the highest conductivity. Conductivity measurements were also carried out in dry oxygen free nitrogen (OFN) and different applied voltage in order to confirm the conduction species of the materials. Doping was carried on the Nb site with the selected dopants, i.e. Ta, W, V, Zr, Ti, Si, Co and Mo in order to enhance the electrical properties of the material. All dopants can be introduced into Bi5NbO10 with rather limited solid solutions. Among the doped materials, Bi5Nb0.95Cu0.05O9.925 exhibited the highest conductivity, which is one order higher than YSZ, which is used as the electrode material in solid oxide fuel cell currently. The activation energy is also comparable to that of YSZ, 0.8 eV. Conductivity of Bi5Nb0.91Zr0.09O9.955 was slightly higher than that of the parent material. No significant difference in conductivity was observed for other doped materials compared to the parent material Bi5NbO10. DTA thermograms of the materials in BixNbOδ (2.5 ≤ x ≤ 6) solid solutions showed that there are no thermal changes and phase transitions were observed. Whereas TGA result indicates that these materials were thermally stable for the temperature range studied. Elemental analysis was carried by inductively coupled plasma-optical emission spectroscopy (ICP-OES). The analysis confirmed the composition of the stoichiometric for single phase material.